2018
DOI: 10.1002/cncr.31382
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the clinical actionability of germline pharmacogenomic findings in oncology

Abstract: Several oncology drugs have actionable germline pharmacogenomic information, justifying their delivery through institutional pharmacogenomic implementations to determine clinical utility. Cancer 2018;124:3052-65. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The use of NGS information (as well as identification of some inherited germline predisposition syndromes) 31 has revolutionized oncology, guiding treatment strategies in up to 20% to 40% of cancer patients 28,29,32‐34 . Less emphasized and much less considered is the evidence supporting therapeutic dosing decisions based on germline pharmacogenomic associations 3,11,13,35 . Our results suggest that the proportion of patients (up to one‐third) who could benefit from their providers considering germline PGx information within just 5 key pharmacogenes is similar to the estimated impact of somatic NGS 28‐30 …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The use of NGS information (as well as identification of some inherited germline predisposition syndromes) 31 has revolutionized oncology, guiding treatment strategies in up to 20% to 40% of cancer patients 28,29,32‐34 . Less emphasized and much less considered is the evidence supporting therapeutic dosing decisions based on germline pharmacogenomic associations 3,11,13,35 . Our results suggest that the proportion of patients (up to one‐third) who could benefit from their providers considering germline PGx information within just 5 key pharmacogenes is similar to the estimated impact of somatic NGS 28‐30 …”
Section: Discussionmentioning
confidence: 67%
“…Many oncology therapies have narrow therapeutic windows and significant interindividual variation in drug response, and these factors may predispose patients to treatment failure and/or harmful adverse drug events (ADEs) 2 . Pharmacogenomics (PGx), the study of how germline genetic variants affect individual response to medications, is a potentially valuable tool that may help optimize the safety of anticancer drug dosing in oncology patients 3 …”
Section: Introductionmentioning
confidence: 99%
“…A lot of work needs to be done in the context of implementation of pharmacogenetics. In a study that analyzed pharmacogenomics literature of 125 drugs used in oncology, more than half of the drugs (55%) did not have pharmacogenomics data while only 12 of those which did, had actionable associations [61] . Understanding the pharmacogenetics of ASNase can help refining treatment strategies for other cancers in which asparagine and/or glutamine depletion can be indicated, such as in subtypes of acute myeloid leukemia, sarcomas, pancreatic and ovarian malignancies [62][63][64][65] .…”
Section: Resultsmentioning
confidence: 99%
“…ACYP2 (Acylphosphatase 2) gene located on chromosome 2p16.2, encodes a small cytosolic acylphosphatase enzyme that catalyzes the hydrolysis of carboxyl‐phosphate bonds (Wellmann et al, ). Genome wide association study has demonstrated that genetic polymorphisms in ACYP2 are associated with telomere length (He et al, ), which has led to studies of the association between ACYP2 and various diseases, including various cancers (Thiesen et al, ).…”
Section: Introductionmentioning
confidence: 99%